Assessment of vagal control of the heart in diabetes. Measures of R-R interval variation under different conditions. Issue 1 (January 1977) - Bennett, T; Fentem, P H; Fitton, D; Hampton, J R; Hosking, D J; Riggott, P A
Abstract : R-R intervals and R-R interval variation were measured in 2 selected groups of diabetic subjects; 1 group was selected because vagal control of the heart appeared normal, the other group was selected because they lacked vagal control of the heart. The means of the R-R intervals for the 2 groups were not significantly different under various conditions (sleeping, lying, during deep breathing, sitting, standing, and during upright activity). The standard deviations of the R-R intervals for the 2 groups were only significantly different during deep breathing and upright activity. It is suggested that cardiac vagal function is not reliably assessed by measurement of R-R interval variation during quiet standing, but useful information may be obtained during deep breathing.